Isothermal Modelling Based Experimental Study of Dissolved Hydrogen Sulfide Adsorption from Waste Water using Eggshell Based Activated Carbon - Habeeb, Omar Abed; K., Ramesh; Ali, Gomaa A. M.; R. M., Yunus (The Malaysian Analytical Sciences Society, 2017)
This paper reports on the experimental work using batch process conducted to determine the adsorption capacity of dissolved hydrogen sulfide in the synthetic wastewater onto the activated carbon which is derived from the eggshell. Fourier Transform Infrared Spectroscopy (FTIR), Energy-Dispersive X-ray Spectroscopy (EDX), Scanning Electron Microscopy (SEM), and particle size distribution have been used to characterize the prepared material. The raw materials of chicken eggshell are adopted to retrieve the carbon content which is then activated using KOH as the activation agent. The examined concentration of dissolved hydrogen sulfide is ranging from 100 to 500 ppm. The maximum adsorption capacity of the dissolved H2S onto the activated carbon is 289.3 mg/g and the equilibrium time is 6 hours. The examined pH value in this study is ranging from 4.5 to 5.5. The two well-known equilibrium adsorption isotherm models, i.e. the Langmuir and the Freundlich models, are employed. It is found that the adsorption isotherm capacity agrees very well to the Freundlich isotherm model. This paper attempts to show the difficulties of converting CaCO 3 to carbon due to the fact that the raw material contains higher calcium (Ca) content instead of carbon. It is concluded that the carbon derived from the chickens’ eggshells is very beneficial for treatment of dissolved H2S in waste water.